The Clinical Relevance of Frequent Germline Genetic Variants Detected by Targeted Sequencing in Patients With Rectal Adenocarcinoma (READ) - HUANG, KEVIN CHIH-YANG (Cancer Genomics Proteomics, 2020)
Background: The progression of colorectal cancer (CRC) mainly stems from the occurrence of somatic mutation. However, there is little information that can be used to comprehensively analyse the importance of germline variants in CRC patients. Patients and Methods: The candidate germline variants between tumor relapse and cured rectal adenocarcinoma (READ) were firstly filtered by whole-exome sequencing (n=4), and validated by targeted sequencing and associated with clinical outcome in READ (n=48). Results: We identified 9 pathogenic germline variants that were clinically associated with survival outcome in READ, including TIPIN, TLR1, TLR10, OR4D6, IGSF3, UBBP4, OR6J1, FAM208A and DISC1. Patients carrying these germline susceptibility variants had an increased risk of poor survival outcome compared to those without these variants. Conclusion: Not only the tumor genome, but also the germline sequence must be analysed to depict the overall genetic profile, providing potential therapeutic strategies for personalized medicine.